Who were those MEN hiding behind the Ulcers? A Case Report - Redzuan, Shazatul Reza Binti Mohd; Liang, Yong Sy (Journal of the ASEAN Federation of Endocrine Societies, 2020)
Multiple endocrine neoplasia type 1 (MEN1) is a rare autosomal dominant disease caused by a mutation in the MEN1 gene. We present a 65-year-old man with MEN1 who has primary hyperparathyroidism, microprolactinoma, meningioma and gastrinoma. He had undergone parathyroidectomy followed by tumour excision of meningioma. The duodenal gastrinoma lesion was inoperable as it was close to the superior mesenteric artery with high surgery risk. Medical therapy with octreotide LAR had been initiated and showed good biochemical response as well as disease progression control. Chemoembolization was proposed if the duodenum lesion reduces in size on maintenance treatment with octreotide LAR. This case highlights the challenges in managing this rare condition and octreotide LAR has shown to be effective in controlling the disease progression in MEN1 with inoperable gastrinoma.